2018
DOI: 10.1073/pnas.1803685115
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and mechanism of human carboxypeptidase O: Insights into its specific activity for acidic residues

Abstract: Human metallocarboxypeptidase O (hCPO) is a recently discovered digestive enzyme localized to the apical membrane of intestinal epithelial cells. Unlike pancreatic metallocarboxypeptidases, hCPO is glycosylated and produced as an active enzyme with distinctive substrate specificity toward C-terminal (C-t) acidic residues. Here we present the crystal structure of hCPO at 1.85-Å resolution, both alone and in complex with a carboxypeptidase inhibitor (NvCI) from the marine snail The structure provides detailed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 62 publications
1
31
1
Order By: Relevance
“…Most notably, the above data confirms that CPO is functional as an enzyme within the early secretory pathway, and suggests a method to examine the intracellular substrate specificity of CPO in living cells. Previous in vitro analyses of CPO substrate specificity indicated that CPO is able to cleave C-terminal glutamate [ 20 ]; cleavage of aspartate was recently demonstrated in vitro [ 21 ]. CPO is unable to cleave C-terminal basic or hydrophobic residues, with the exception of a very weak ability to cleave C-terminal alanine, and the cleavage of polar amino acids has not yet been investigated [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, the above data confirms that CPO is functional as an enzyme within the early secretory pathway, and suggests a method to examine the intracellular substrate specificity of CPO in living cells. Previous in vitro analyses of CPO substrate specificity indicated that CPO is able to cleave C-terminal glutamate [ 20 ]; cleavage of aspartate was recently demonstrated in vitro [ 21 ]. CPO is unable to cleave C-terminal basic or hydrophobic residues, with the exception of a very weak ability to cleave C-terminal alanine, and the cleavage of polar amino acids has not yet been investigated [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…While other digestive CPs had a prodomain thought to be necessary for folding and regulation [ 18 , 19 ], CPO lacked this feature and was predicted to be an inactive carboxypeptidase homolog. It has now been shown that CPO produces a fully functional enzyme even in the absence of a prodomain, is GPI-anchored, and is expressed on the surface of intestinal enterocytes where it likely processes dietary proteins and peptides [ 20 , 21 ]. The ability of CPO to cleave C-terminal acidic amino acids suggests that CPO complements the functions of CPA and CPB in the digestion of dietary proteins [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…2). CPA-like enzymes are predicted to cleave aliphatic or aromatic C-terminal amino acids due to a hydrophobic amino acid at the bottom of their speci city pocket (residue 255 in bovine CPA1), while CPBlike enzymes are predicted to cleave basic C-terminal amino acids with an acidic amino acid, often aspartic acid, at their residue 255 equivalent [18]. Fungal proteins identi ed within the CPB clade often had an Asp at position 255; however, a lot of variation was seen at this position, as nearly every amino acid was represented.…”
Section: Phylogenetic Analysis Of Fungal Ecm14mentioning
confidence: 99%
“…This ambiguity is further supported by the fact that the active site residues from these basal fungi enzymes are not at all different, all exhibiting CPA-like character. CPA-like enzymes are predicted to cleave aliphatic or aromatic C-terminal amino acids due to a hydrophobic amino acid at the bottom of their speci city pocket (residue 255 in bovine CPA1), while CPBlike enzymes are predicted to cleave basic C-terminal amino acids with an acidic amino acid, often aspartic acid, at their residue 255 equivalent [18].…”
Section: Phylogenetic Analysis Of Fungal Ecm14mentioning
confidence: 99%